Bulgaria : 2016 Article IV Consultation-Press Release; Staff Report; and Statement by the Executive Director for Bulgaria. (IMF Staff Country Reports; Country Report, 2016)
The Bulgarian economy has shown resilience since the last Article IV consultation. Growth over the last 4 quarters exceeded expectations. The authorities took concrete steps to correct the fiscal slippage in 2014 and efforts are underway to strengthen confidence in the health of the financial system. Looking ahead, risks to the outlook are broadly balanced. Downside risks stem mostly from weak external demand, possible regional tension, and reversal in domestic policy reforms.